Students’ Saving Attitude: Does Parents’ Background Matter - Norasikin Salikin; Norailis Ab Wahab; Nurazalia Zakaria; Rosnia Masruki; Siti Nurulhuda Nordin (International Journal of Trade, Economics and Finance, 2024)
Volume: 3 No: 6 (page: 479-484)